Effect of Leg Half-Squat Training With Blood Flow Restriction Under Different External Loads on Strength and Vertical Jumping Performance in Well-Trained Volleyball Players. Issue 3 (19th September 2022) - Wang, Jiaoqin; Fu, Honghao; QiangZhang,; Zhang, Ming; Fan, Yongzhao
Purpose: To examine the effect of blood flow restriction resistance training under different external loads on the muscle strength and vertical jumping performance in volleyball players. Methods: 18 well-trained collegiate male volleyball players were randomly divided into 3 groups: high-load resistance training group (HL-RT, 70% 1RM, n = 6), low-load blood flow restriction resistance training group (LL-BFR-RT, 30% 1RM, 50% arterial occlusion, n = 6), and high-load blood flow restriction resistance training group (HL-BFR-RT, 70% 1RM, 50% arterial occlusion, n = 6). Participants performed leg half-squat exercise 3 times per week for 8 weeks. Measurements of Isokinetic peak torque of knee extension and flexion, 1RM leg half-squat, squat jump, and 3 footed take-off were obtained before and after training. A two-way repeated-measures analysis of variance was used to examine differences among the 3 groups and between the 2 testing time (pre-test vs post-test). Results: (1) The HL-RT group was significantly greater in muscle strength than that in the LL-BFR-RT group ( P < .05), but no improvement in vertical jumping performance ( P >.05). (2) Improvement in muscle strength and vertical jumping performance was significantly greater in the HL-BFR-RT group than that in the LL-BFR-RT group ( P <.05). (3) The HL-BFR-RT group had greater but not significant improvement in muscle strength and vertical jumping performance than that in the HL-RT group. Conclusions: Although increases in muscle strength were observed between training groups, HL-BFR-RT increased not only muscle strength but vertical jumping performance to a greater extent compared to LL-BFR-RT and HL-RT.